Protótipo de microestação meteorológica de baixo custo para monitoramento de variáveis microclimáticas - Leite Júnior, Mirabor José (2022)
Fruit farming has been standing out as one of the main agricultural activities in the country, exerting great influence on the social and economic sector. This is linked to some important factors, such as the generation of employment and income in small areas and the high added value in its product. Still because it is an activity performed, most of the time, in a manual and conventional way, fruit farming has a great potential for technological growth, especially when adopting the concepts applied by Precision Agriculture (PA) on the cultures of grains, fibers and energy, creating a new segment: the Precision Fruticulture. For being it is an activity that depends on climatic factors that in most cases cannot be controlled, the monitoring of environmental variables is an important tool for planning actions in the orchard, whether preventive or corrective. In the apple culture, for example, producers have adopted alternatives to prevent damage caused by bad weather, such as covering orchards with anti-hail screens. This action has been proving to be the most effective alternative to avoid damage to plants and fruits, and economic losses caused by hail, with an expected evolution to cover 80% of the production area in the next few years. However, the use of this system alters the microclimate conditions in comparison with the management used in plants grown in full sun, and therefore requires different management. In addition, traditional meteorological data are obtained under open-air conditions, under different climatic conditions than the way orchards are being conducted under canvas. To meet this growing demand for information and technology in the area of fruit growing, this work aims to develop a prototype of a micro meteorological station, of low cost, to be attached directly to the plant, which can be installed in plants with and without canvas cover, collecting data of air temperature, relative humidity, solar radiation, soil moisture and leaf wetting. The prototype was built using the Arduino standard, a reference in DIY projects. Besides the sensors, the station also has a data storage module to be processed and interpreted by the end user. As a result, the built device proved to be able to collect data as efficiently as commercial and official INMET weather stations, through validation tests in the lab and in the field. It is worth mentioning its low manufacturing cost (R$ 456.80), the ease of replication and adaptation to other agricultural activities by adding more or less sensors, or even the possibility of integrating, from future work, wireless data transmission systems.